Total synthesis of the post-translationally modified polyazole peptide antibiotic plantazolicin A - Wada, Hiroki; Williams, Huw E. L.; Moody, Christopher J. (Wiley-VCH Verlag, 2015)
The power of rhodium carbene methodology in chemistry is demonstrated by the synthesis of a structurally complex polyazole antibiotic. Plantazolicin A, a novel soil bacterium metabolite, comprises a linear array of 10 five-membered rings in two pentacyclic regions that derive from ribosomal peptide synthesis followed by extensive post-translational modification. The compound possesses potent antimicrobial activity, and is selectively active against the anthrax causing organism. A conceptually different synthesis of plantazolicin A is reported in which the key steps are the use of rhodium(II)-catalyzed reactions of diazocarbonyl compounds to generate up to six of the seven oxazole rings of the antibiotic. NMR Spectroscopic studies and molecular modeling, reveal a likely dynamic hairpin conformation with a hinge region around the two isoleucine residues.The compound has modest activity against methicillin-resistant Staphylococcus aureus (MRSA).